2001
DOI: 10.1128/iai.69.3.1747-1754.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C-Reactive Protein in the Human Respiratory Tract

Abstract: C-reactive protein (CRP) is a normal constituent of human sera synthesized by hepatocytes and induced by proinflammatory cytokines. The function of this acute-phase reactant includes activation of complement and enhancement of opsonophagocytosis. CRP binds to phosphorylcholine (ChoP), a constituent of eukaryotic membranes that is also found on the cell surface of major bacterial pathogens of the human respiratory tract, including Streptococcus pneumoniae and Haemophilus influenzae. The presence of CRP on mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 48 publications
5
129
0
2
Order By: Relevance
“…[5][6][7][8][9] Two studies have shown that both epithelial cells of the respiratory tract and renal epithelium produce CRP. 14,18 Moreover, neuronal cells also Figure 1. Effect of cytokine and LPS treatment on CRP protein production in HCASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Two studies have shown that both epithelial cells of the respiratory tract and renal epithelium produce CRP. 14,18 Moreover, neuronal cells also Figure 1. Effect of cytokine and LPS treatment on CRP protein production in HCASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider early prostate neoplasia progression, where repeated bouts of injury and cell death to the prostate epithelium occur as a result of the action of inflammatory cells in response to pathogens or autoimmune disease (phagocytic cells at inflammatory sites generate reactive oxygen and nitrogen species, which damage cells and the genome) or from direct injury from circulating carcinogens/toxins in the urine, the injury caused to the epithelium triggers a restorative epithelial cell proliferation to replace the damaged cells (Coussens and Werb, 2002;De Marzo et al, 2007 (Haider et al, 2006), and at least epithelial cells of the respiratory tract are capable of CRP expression and secretion (Gould and Weiser, 2001). If local inflammation resolution is dysregulated, the cellular response to the pattern of chronic inflammation changes, such that macrophages and other inflammatory cells generate a great amount of growth factors, cytokines and reactive oxygen species that may cause DNA damage and predispose the patient to neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…CRP may also play a role in mucosal immunity, since it is present in human nasal secretions and since CRP gene expression has been detected in epithelial cells from nasal polyps and in pharyngeal cell lines (19). Mucosal CRP can bind to PC on the surface of H. influenzae and S. pneumoniae and prevent PC-mediated attachment to epithelial cells via the plateletactivating factor receptor (18).…”
Section: Discussionmentioning
confidence: 99%